Acute tissue reactions, inner segment pathology, and effects of the antioxidant α1-microglobulin in an in vitro model of retinal detachment. (August 2018) - Ghosh, Fredrik; Åkerström, Bo; Bergwik, Jesper; Abdshill, Hodan; Gefors, Lina; Taylor, Linnéa
Abstract: The purpose of this study was to explore acute tissue reactions, ultrastructural photoreceptor morphology with emphasis on inner segments, and the effect of antioxidant treatment in an in vitro model of rhegmatogenous retinal detachment (RRD). A previously described method of RRD simulation was used with adult retinal porcine explants kept free-floating in culture medium with or without treatment with the radical scavenger α1 -microglobulin (A1M). Explants were examined at 5 time points from 1 to 24 h using transmission electron microscopy as well as quantitative real-time PCR (RT-PCR) to quantify gene expression of the cell stress marker heat shock protein 70 (Hsp70) and oxidative stress marker heme oxygenase (HO-1). The culture medium level of the cell damage marker lactate dehydrogenase (LDH) and oxidative stress DNA damage marker 8-Oxo-2′-deoxyguanosine (8-OHdG) was also assessed at each time point. We found that the levels of Hsp70 and LDH rapidly increased in both groups, and at 3 and 6 h, Hsp70 was significantly higher in A1M treated retinas. At 24 h, Hsp70 and LDH, as well as 8-OHdG were significantly lower compared with controls, whereas the tissue level of HO-1 was significantly higher. Progressive ultrastructural photoreceptor changes were seen in untreated control explants from 1 h and onwards including outer segment shortening and loss, disruption of organelles within the inner segments and loss of perikarya in the outer nuclear layer. Inner segment pathology was more rapid and extensive in rods compared with in cones. In A1M treated counterparts, damage to rod inner segment mitochondria was significantly higher after 1 h of culture, but after this time, no statistical difference was found. At 24 h, cone inner segment mitochondrial disruption was significantly higher in control retinas and the number of surviving perikarya lower. From our results, we conclude that retinal explants elicit acute cell stress reactions when placed in culture without physical support simulating a detached retina floating in the vitreous space. Photoreceptors rapidly display degenerative changes including extensive damage to inner segment mitochondria indicating loss of energy transduction as an early key event. A1M increases initial mitochondrial stress in the rods, however, subsequent pathology is attenuated by the treatment, highlighting the dynamics of protective as well as disruptive oxidative stress reactions in the detached retina. Highlights: Retinal explants show acute cell stress reactions when placed in culture without tissue support simulating a detached retina. Photoreceptors display acute degenerative changes including extensive damage to inner segment mitochondria indicating. Treatment with the radical scavenger A1M increases initial mitochondrial damage, however, subsequent pathology is attenuated.